Media Redundancy and Crisis Communication Resilience in Rural Communities: Community Radio Practices in Cisewu, Indonesia - Dian Wardiana Sjuchro; Agus Rahmat; Iriana Bakti; Nuryah Asri Sjafirah; Ronny Yudhi Septa Priana (CV. Media Digital Publikasi Indonesia, 2026)
Communication networks and systems in rural areas often experience obstacles, especially during times of crisis due to disasters due to infrastructure damage and other disruptions that result in limited communication and information channels. This study aims to reveal how community radio contributes to the communication resilience system in facing crises in rural areas. The community radio referred to in this study is the RaSi FM Community Radio in Cisewu Village, Garut Regency, West Java, Indonesia. This research is a qualitative study using a case study approach. Researchers obtained data through in-depth interviews involving community radio managers and local residents and participant observation. The data analyzed included interview results, broadcast content, and other data deemed relevant to the study. The research findings indicate that community radio can function as an alternative communication channel that can replace other communication tools that experience obstacles and disruptions such as internet connections, telecommunication network interruptions, especially during crises such as natural disasters. Community radio provides verifiable information about the current conditions for both the surrounding community and those still within the limited service coverage area. In addition to the information provided, the presence of community radio encourages social coordination within the community and produces a collective response to various potential risks that may arise. These findings suggest that redundancy through community media can strengthen communication resilience in rural crisis systems.